Brief communications: changes in inflammatory biomarkers and lipid profiles after switching to long-acting cabotegravir plus rilpivirine - Adachi, Eisuke; Saito, Makoto; Otani, Amato; Koga, Michiko; Yotsuyanagi, Hiroshi (AIDS research and therapy, 2024)
We assessed whether the impact of cabotegravir plus rilpivirine on inflammation reduction differs from that of oral antiretrovirals, using real-world data. Inflammatory biomarkers and lipid profiles were followed from baseline to 8 months after switching. Seventy-eight participants were analyzed. The CD4/CD8 ratio and C-reactive protein did not change. There were transient decreases in CD8 and CD4 counts in the group that switched from the dolutegravir-based regimen, but not in the tenofovir alafenamide-based regimen group. High-density lipoprotein (HDL) cholesterol increased, resulting in a decrease in the total-cholesterol to HDL cholesterol ratio, whereas there was no significant change in low-density lipoprotein cholesterol.